Death anxiety and religiosity in a multicultural sample: a pilot study examining curvilinearity, age and gender in Singapore - Belak, Radiah Maria; Goh, Kay Hee (Frontiers in Psychology, 2024)
This study investigated the association between multidimensional death anxiety and religiosity in multicultural Singapore by examining potential variations by age and gender. We also explored the possibility of a curvilinear effect, where highly religious or non-religious individuals report lower death anxiety than moderately religious people, forming an inverted U-curve pattern. Data were collected from 110 participants using questionnaires that assessed death anxiety and religiosity. Parametric and non-parametric tests were then conducted. The findings showed that women had significantly higher death anxiety and religiosity than men, and highly and moderately religious people had significantly higher death anxiety than non-religious people. People of all age groups had similar levels of death anxiety. These findings highlight the importance of developing targeted death anxiety interventions that integrate spiritual aspects in Singapore so that clinicians can provide culturally competent care.